2015
DOI: 10.1539/joh.14-0136-oa
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of perfluoroalkyl carboxylic acids with different carbon chain lengths in mice and humans

Abstract: FUJII, et al.: Toxicokinetics of perfluoroalkyl carboxylic acids observed in the corresponding partition ratio in humans (CSF/serum). Conclusions: The large sequestration volumes of PFCAs in the liver seem to be attributable to the liver's large binding capacity in both species. This will be useful in evaluating PFCA bioaccumulation in other species. (J Occup Health 2015; 57: 1-12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 38 publications
6
67
0
Order By: Relevance
“…2), suggesting different bioaccumulation mechanisms. This result may be explained by previous in vivo and in vitro studies, showing that long-chain PFCAs may accumulate preferentially in liver over lipid-rich tissues due to a high affinity for fatty acid binding proteins in the liver (Fujii et al, 2015;Zhang et al, 2013).…”
Section: Correlations Between Pfcas and Classical Popsmentioning
confidence: 78%
See 1 more Smart Citation
“…2), suggesting different bioaccumulation mechanisms. This result may be explained by previous in vivo and in vitro studies, showing that long-chain PFCAs may accumulate preferentially in liver over lipid-rich tissues due to a high affinity for fatty acid binding proteins in the liver (Fujii et al, 2015;Zhang et al, 2013).…”
Section: Correlations Between Pfcas and Classical Popsmentioning
confidence: 78%
“…Moreover, the result of the PCA may also reflect the different bioaccumulation mechanisms of the studied compounds. PFOA (C8) has both hydrophobic and hydrophilic regions and tends to accumulate in serum due to its binding affinity to serum proteins (Fujii et al, 2015;Jones et al, 2003). On the other hand, the long-chain PFCAs are known lipophilic contaminants, since the lipophilicity increases with increasing chain lengths and are anticipated to have a similar distribution pattern to the lipophilic POPs, which accumulate in lipid-rich tissues.…”
Section: Correlations Between Pfcas and Classical Popsmentioning
confidence: 99%
“…Bile acids are excreted into the intestine and reabsorbed, and similar enterohepatic circulation has been suggested for PFOS and PFOA 22,23 . It has been estimated that over 90% of PFOS and PFOA have to be reabsorbed in order to explain the long half-life of these compounds in humans 24,25 . Bile acids can therefore potentially act as mediators, linking PFAS exposures and altered lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The M/P concentration ratio is used as a standard indicator of breastmilk transferability of chemicals [9]. Our previous study showed that PFCAs (C8 to C13) in plasma increase in the 6-12 h after administration and become stable within 24 h [20]. Based on this finding, we collected plasma and milk at 24 h after administration.…”
Section: M/p Concentration Ratiomentioning
confidence: 99%
“…Previously, we investigated the pharmacokinetics and mass balance of injected PFCAs in male and nonpregnant female mice [20]. The toxicokinetics were significantly different among PFCAs, indicating that lactational transfer could also depend on PFCA chain length.…”
Section: Introductionmentioning
confidence: 99%